Radiation Impact of the Halloween GLE Events During the October–November 2003 Period - N. Larsen; A. Mishev (Space Weather)
Abstract From late October to early November 2003, one of the strongest recorded geomagnetic storms occurred due to heightened solar activity. Three ground‐level enhancement events (GLEs) took place during this period, GLE 65, 66, and 67, known as the Halloween events. In this work we expand upon and use, the newly developed and verified dosimetric model Oulu CRAC:DOMO (Cosmic Ray Atmospheric Cascade: Dosimetric Model) to compute the radiation impact of the Halloween events at an altitude typical for aviation, that is of 35 kft. Complex magnetospheric modeling was performed for each GLE event and the deep Forbush decrease present was reconstructed and accounted for. Using a conservative approach, the computed total effective dose for all three Halloween GLEs was 135 μSv in polar regions, an increase of 129% above the galactic cosmic ray background induced dose. While this is a significant increase, we conclude that the radiation hazard posed to aircrew and passengers was relatively minor. In addition, a comparison between flight dosimetric measurements taken during the Halloween events and CRAC:DOMO showed a good agreement.